The Impact of Shadow Banking on the Financial Stability: Evidence from G20 Countries - Seyed Hossein Mirjalili; Marziyeh Esfandiary; Mehran Zarei (Journal of Money and Economy, 2021)
Shadow banking is a term that came out of the financial crisis of 2007-2009. There is a belief that shadow banking was one of the crisis reasons. Because the excessive expansion of shadow banking endangers the financial stability of countries, this paper examines the impact of shadow banking on financial stability using data from 14 countries of the G20 during 2002-2018. We divided countries into four groups according to the level of shadow banking activity; then, we employed the quantile regression method. The results indicated that shadow banking hurts financial stability (positive impact on financial instability) in countries with a high shadow banking index (fourth group countries). One unit of increase in the shadow banking index increases financial instability in the fourth group countries (high shadow banking) by 1.6 units. But in countries where shadow banking is not very strong (other three groups), shadow banking does not significantly affect financial stability.
Keywords: 330; Shadow Banking; Financial Stability; Quantile Regression; G20